(untitled) (Journal of Economic Research & Business Administration, 2015)
The article describes the theoretical and practical issues of Eurasian integration capabilities in the development of regional innovation system regions of the CU and CES in innovation. It is established that in innovative, educational and scientifi c spheres can signifi cantly extend the range of partners and a range of opportunities to enhance the research and innovation activities in the future. Availability of traditional links with neighboring countries indicates considerable potential in this area. However, there are still undiscovered potential for signifi cant improvement, and not having the ability to be used until the end. There is no more clear national strategy aimed at the potential of these integration processes. Institutions particularly at the sub national level, not quite ready to establish relationships in the broader regional context. Customs union increases competitive pressure not only on the company but also for scientifi c institutions. This pressure also creates new opportunities and if prospects improved to meet the needs of future customers, including through the intensifi cation of innovation.